If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 39b = 14 + 3b Reorder the terms: 39b + 2x = 14 + 3b Solving 39b + 2x = 14 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 39b + -3b + 2x = 14 + 3b + -3b Combine like terms: 39b + -3b = 36b 36b + 2x = 14 + 3b + -3b Combine like terms: 3b + -3b = 0 36b + 2x = 14 + 0 36b + 2x = 14 Add '-2x' to each side of the equation. 36b + 2x + -2x = 14 + -2x Combine like terms: 2x + -2x = 0 36b + 0 = 14 + -2x 36b = 14 + -2x Divide each side by '36'. b = 0.3888888889 + -0.05555555556x Simplifying b = 0.3888888889 + -0.05555555556x
| 2v-6=-2v+6+7-3 | | 6(-3-7)= | | X+(x*0.087)=y | | 9y+6(4y-3)=5(y-7) | | 32w^2+32w+8=0 | | 1/3w9 | | 6u+8v-7-6u-4v+8w= | | -4(1+b)+8b=-14+2b | | -192=8(4x-8) | | x^2=x-57 | | 15/50=3x | | 5x(x+3)+6(x+3)= | | 6(k+7)=18+2k | | -9/4=r-4/5 | | 8x+4(x-7)=3(8-x)+12 | | 3c+7+12c=53 | | 32+n+n=126 | | 36x^2y-18xy^2+2y^3= | | -31/2x=14 | | m-5m-8=3+(-7)+m | | 4x-10=-6x+3 | | (N+4)*5=65 | | 79-(5x+16)=5(x+6)+x | | g(x)=2x-1 | | 3x^2-17x-12=0 | | 4x-7=3(2+1) | | 6:?x10/2 | | 9-4x[3-(7-2)/2] | | 8X(2X-3)-4X(4x-1)=40 | | 8x+6y=4 | | 100a-a^2-2484=0 | | 10m+6=56 |